Recurrent Respiratory Papillomatosis Office versus Operating Room: Systematic Review and Meta-Analysis. (March 2021) - Chen, Sophia; Connors, Joseph; Zhang, Yan; Wang, Binhuan; Vieira, Dorice; Shapira-Galitz, Yael; Garber, David; Amin, Milan R.
Objectives: Recurrent respiratory papillomatosis can be treated in the office or operating room (OR). The choice of treatment is based on several factors, including patient and surgeon preference. However, there is little data to guide the decision-making. This study examines the available literature comparing operative treatment in-office versus OR. Methods: A systematic review was performed following Preferred Reporting Items for Systematic Reviews guidelines. Of 2, 864 articles identified, 78 were reviewed full-length and 18 were included. Outcomes of interest were recurrence and complication rates, number of procedures, time interval between procedures, and cost. Results: Only one study compared outcomes of operative in-office to OR treatments. The weighted average complication rate for OR procedures was 0.02 (95% confidence interval [CI] 0.00-0.32), n = 8, and for office procedures, 0.17 (95% CI 0.08-0.33), n = 6. The weighted average time interval between OR procedures was 10.59 months (5.83, 15.35) and for office procedures 5.40 months (3.26-7.54), n = 1. The weighted average cost of OR procedures was $10, 105.22 ($5, 622.51-14, 587.83), n = 2 versus $2, 081.00 ($1, 987.64-$2, 174.36), n = 1 for office procedures. Conclusion: Only one study compares office to OR treatment. The overall data indicate no differences aside from cost and imply that office procedures may be more cost-effective than OR procedures. However, the heterogeneous data limits any strong comparison of outcomes between office and OR-based treatment of laryngeal papillomas. More studies to compare the two treatment settings are warranted.